Determination of Patient Energy Requirements by Registered Dietitian Nutritionists in Inpatient and Outpatient Settings. Issue 1 (January 2017) - Herrington, Holly; Gregoire, Mary; Foley, Sharon; Roehl, Kelly
Abstract : This study examined whether and how registered dietitian nutritionists (RDNs) determine energy requirements for their patients/clients. A total of 5000 RDNs were asked to participate in an online questionnaire; 1019 responded (20.4%). Most RDNs (93.4% inpatient and 84.6% outpatient) used predictive equations; less than one-fourth of dietitians used indirect calorimetry to determine energy requirements. Use of indirect calorimetry did not differ on the basis of most demographic characteristics. Inpatient RDNs more often used a metabolic cart (17.2%) than handheld device (1.5%). Outpatient RDNs chose handheld calorimeters (10.7%) more often than metabolic carts (9.1%).